Hadis Meneguk Air Perlahan: Implementasi dalam Kesehatan - Firman, Firman; Hasbi, M. Ridwan; Kulsum, Fajar Maulani (Jurnal An-Nur, 2024)
Thirst is a normal condition that occurs in daily life and usually happens because the body needs fluids to carry out metabolism. However, many people, especially Muslims, consider drinking water as trivial and rarely pay attention to proper etiquette when drinking water. In fact, it has been explained in the hadith that the etiquette of drinking water is to do it slowly. The research methodology used in this study is qualitative, which emphasizes analysis or description to explain phenomena in depth by collecting as much data as possible. The results of this study show that Prophet Muhammad explained the etiquette of drinking water in the hadith. One of the etiquettes is to drink water slowly in one gulp, two gulps, or three gulps. The implementation of this hadith in the field of health is to encourage people to consume water without rushing, thus assisting in better nutrient absorption, optimizing body hydration, preventing excessive burden on the kidneys, and avoiding the risk of dangerous diseases such as water diuresis and hyponatremia.